Development of hybrid and templated silica-p123 membranes for brackish water desalination - Muthia Elma; Dwi Rasy Mujiyanti; Noor Maizura Ismail; Muhammad Roil Bilad; Aulia Rahma; Sazila Karina Rahman; Fitriani Fitriani; Arief Rakhman; Erdina Lulu Atika Rampun (MDPI, 2020)
Water scarcity is still a pressing issue in many regions. The application of membrane technology through water desalination to convert brackish to potable water is a promising technology to solve this issue. This study compared the performance of templated TEOS-P123 and ES40-P123 hybrid membranes for brackish water desalination. The membranes were prepared by the sol–gel method by employing tetraethyl orthosilicate (TEOS) for the carbon-templated silica (soft template) and ethyl silicate (ES40) for the hybrid organo-silica. Both sols were templated by adding 35 wt.% of pluronic triblock copolymer (P123) as the carbon source. The silica-templated sols were dip-coated onto alumina support (four layers) and were calcined by using the RTP (rapid thermal processing) method. The prepared membranes were tested using pervaporation set up at room temperature (~25 ◦C) using brackish water (0.3 and 1 wt.%) as the feed. It was found that the hybrid membrane exhibited the highest specific surface area (6.72 m² ·g⁻¹), pore size (3.67 nm), and pore volume (0.45 cm³ ·g⁻¹). The hybrid ES40-P123 was twice thicker (2 µm) than TEOS-P123-templated membranes (1 µm). Lastly, the hybrid ES40-P123 displayed highest water flux of 6.2 kg·m⁻² ·h⁻¹. Both membranes showed excellent robustness and salt rejections of >99%.